Towards Numerical Simulation Tool of Motion Solid Particles in Fluid Flow - S Zouaoui; H Djebouri; B Ferhat; K Mohammedi (International Journal of Multiphysics, 2021)
We present here a numerical method to compute the motion of rigid particles in fluid flow with a non-elastic impact law. Many methods have been proposed recently and different strategies have been used to compute such flows. Our motivation is the handling of the non-overlapping constraint in fluid-particle direct simulations. Each particle is treated individually and the Navier-Stokes equations are solved for the moving fluid by Fluent code which is based on the Finite Volume Method. The contact-handling algorithm, which is implemented in a research C ++, is based on the projection of the velocity field of the rigid particles over the velocity field of the fluid flow. The method consists of imposing a constraint on the velocity field of the particles, as a guarantee that at each time step the calculated particle velocity field belongs to an eligible velocity field of the fluid. In this case study, an Uzawa algorithm has been applied.